A lead-calcium-tin-aluminum multi-element alloy, a preparation method and application thereof
Patent Information
- Application Number
- CN202611460118.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-23
AI Technical Summary
针对现有技术的不足,本发明提供了一种铅钙锡铝多元合金及其制备方法与应用,解决了现有合金材料力学性能差、耐腐蚀性能不足、使用寿命有限的问题
(1)本发明采用改性碳化钛作为增强相引入铅钙锡铝多元合金体系。碳化钛具有较高的熔点、优异的化学稳定性以及较高的硬度,可作为异质形核位点,促进晶粒细化,抑制晶粒异常长大;同时,碳化钛能够在合金基体中形成弥散增强相,通过钉扎作用限制晶界迁移,提高合金组织稳定性,并改善板栅材料在长期充放电循环过程中的结构稳定性。本发明通过化学镀镍方式对碳化钛进行表面改性,利用镍与铅基熔体的良好润湿性,改善碳化钛在液态铅中润湿差、易团聚、界面结合弱的问题。将纳米碳化钛加入无水乙醇中进行超声分散,使团聚的纳米碳化钛充分分离,提高颗粒表面暴露程度。随后加入盐酸溶液进行酸处理,利用酸性环境去除纳米碳化钛表面的杂质及弱结合氧化物,提高颗粒表面活性。进一步地,将预处理碳化钛加入氯化亚锡溶液中,使Sn2+吸附于纳米碳化钛表面形成敏化层,为后续钯活化提供还原位点。随后加入氯化钯溶液中,利用Sn2+与Pd2+之间的氧化还原反应,使Pd沉积于碳化钛表面,形成均匀分布的催化活性中心,为化学镀镍反应提供成核基础。之后,将活化碳化钛混合液加入化学镀镍液中,在次磷酸钠还原作用下,Ni2+在Pd催化作用下发生还原沉积,同时部分磷元素进入镀层形成Ni-P包覆层。镍具有良好的金属性和导电性,可改善碳化钛与铅基熔体之间的润湿性能,降低增强相团聚现象,提高碳化钛与铅基体之间的界面结合强度,有利于碳化钛在合金内部实现更均匀的分散。因此,通过酸处理、敏化、活化以及化学镀镍处理,在碳化钛表面构建金属镍过渡层,使陶瓷增强相与金属基体之间形成良好的界面结合,有利于发挥碳化钛的晶粒细化和增强作用,提高铅基合金的组织稳定性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lead-acid battery technology, specifically a lead-calcium-tin-aluminum multi-element alloy, its preparation method, and its application. Background Technology
[0002] The grid is a core component of lead-acid batteries, responsible for conducting current, supporting active materials, and maintaining electrode stability. Early lead-acid battery grids primarily used lead-antimony alloys, but these alloys were prone to increased gas evolution, electrolyte loss, and accelerated self-discharge during use, failing to meet the demands of modern maintenance-free lead-acid batteries. Subsequently, lead-calcium alloys, due to their higher hydrogen evolution overpotential and lower gas evolution rate, gradually became an important material for maintenance-free lead-acid battery grids. However, single lead-calcium alloys still suffer from insufficient grain structure stability, limited corrosion resistance, and decreased mechanical properties during long-term cycling. To further improve the overall performance of lead-calcium alloy grids, alloying elements such as tin and aluminum are typically introduced to form multi-element alloys. Tin improves the alloy's corrosion resistance and casting properties; some tin dissolves in the lead matrix, producing a solid solution strengthening effect and increasing matrix strength. The addition of aluminum promotes the formation of a stable protective oxide film on the alloy surface, improving corrosion resistance.
[0003] Chinese patent application CN103985879A discloses a lead-calcium-tin-aluminum positive electrode grid alloy and its preparation method. This invention uses lead sheet to wrap a uniformly mixed mixture of calcium shavings and aluminum flakes, pressing it into molten lead, eliminating the need for a calcium-aluminum master alloy smelting process. The prepared alloy exhibits excellent comprehensive mechanical properties, effectively reducing oxide film impedance, mitigating early capacity decay and thermal runaway swelling in lead-acid batteries, and improving deep cycle life. However, this alloy primarily improves performance by adjusting the addition of calcium and aluminum elements; further optimization is needed in the research of multi-element synergistic regulation of alloy microstructure and long-term service stability. Chinese patent application CN101237045A discloses a multi-element alloy for fabricating lead-acid battery grids. This alloy contains lead, calcium, tin, aluminum, and bismuth, exhibiting high hydrogen evolution potential and strong corrosion resistance. It improves the recombination efficiency of oxygen inside the battery at the negative electrode, increases the charge acceptance and over-discharge resistance of the positive electrode during deep discharge cycles, and significantly improves the cycle life of the resulting lead-acid battery. However, this alloy involves the synergistic addition of multiple alloying elements, and the interaction between these elements and the uniformity of the microstructure still need further optimization to meet the long-term service requirements of high-performance lead-acid batteries.
[0004] Therefore, developing a lead-calcium-tin-aluminum multi-element alloy with high mechanical properties, excellent corrosion resistance, and long service life is an urgent problem to be solved.
[0005] Summary of the Invention (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a lead-calcium-tin-aluminum multi-element alloy, its preparation method, and its application, solving the problems of poor mechanical properties, insufficient corrosion resistance, and limited service life of existing alloy materials.
[0006] (II) Technical Solution To achieve the above objectives, the present invention discloses a lead-calcium-tin-aluminum multi-element alloy, wherein the lead-calcium-tin-aluminum multi-element alloy is composed of the following components by mass percentage: calcium 0.06%-0.1%, tin 1.2%-2%, aluminum 0.01%-0.03%, indium 0.02%-0.08%, tellurium 0.01%-0.04%, modified titanium carbide 0.1%-0.3%, and the balance being lead.
[0007] The modified titanium carbide is a nickel-phosphorus coated titanium carbide composite reinforcing material, which is obtained by depositing a nickel-phosphorus coating layer on the surface of pretreated titanium carbide using a chemical nickel plating process.
[0008] Preferably, the method for preparing the modified titanium carbide includes the following steps: S1. Add nano-titanium carbide to anhydrous ethanol, ultrasonically disperse for 20-30 min, add hydrochloric acid solution, stir at 20-30℃ for 40-60 min, after the reaction is completed, centrifuge, wash with deionized water until neutral, and dry at 60-80℃ for 12-24 h to obtain pretreated titanium carbide. S2. Disperse stannous chloride in hydrochloric acid solution, add the pretreated titanium carbide, stir at 20-30℃ for 15-30 min, centrifuge, and wash with deionized water 2-3 times to obtain sensitized titanium carbide mixture; S3. Disperse palladium chloride in hydrochloric acid solution, add the sensitized titanium carbide mixture, stir at 20-30℃ for 15-25 min, centrifuge, and wash with deionized water 2-3 times to obtain activated titanium carbide mixture; S4. Disperse nickel sulfate hexahydrate in deionized water, add sodium citrate and sodium hypophosphite in sequence, adjust the pH of the system to 8-10 with ammonia water to obtain a chemical nickel plating solution, add the activated titanium carbide mixture to the chemical nickel plating solution, react at 75-90℃ for 60-80 min, after the reaction is completed, centrifuge, wash, and dry at 60-80℃ for 12-24 h to obtain modified titanium carbide.
[0009] Preferably, the particle size of the nano-titanium carbide in S1 is 80-120 nm.
[0010] Preferably, the hydrochloric acid solution in S1 is a 0.2-0.5 mol / L hydrochloric acid aqueous solution.
[0011] Preferably, during the centrifugation process in S1, the rotation speed is 6000-8000 r / min and the time is 5-10 min.
[0012] Preferably, the mass ratio of nano-titanium carbide, anhydrous ethanol, and hydrochloric acid solution in S1 is 1:(10-15):(10-15).
[0013] Preferably, the hydrochloric acid solution in S2 is a 1-3 mol / L hydrochloric acid aqueous solution.
[0014] Preferably, during the centrifugation process in S2, the rotation speed is 6000-8000 r / min and the time is 5-10 min.
[0015] Preferably, the mass ratio of stannous chloride, hydrochloric acid solution, and pretreated titanium carbide in S2 is (0.3-0.8):(25-40):1.
[0016] Preferably, the hydrochloric acid solution in S3 is a 0.5-1 mol / L hydrochloric acid aqueous solution.
[0017] Preferably, during the centrifugation process in S3, the rotation speed is 6000-8000 r / min and the time is 5-10 min.
[0018] Preferably, the mass ratio of palladium chloride, hydrochloric acid solution, and sensitized titanium carbide mixture in S3 is (0.03-0.08):(25-40):1.
[0019] Preferably, the concentration of ammonia in S4 is 25%-28%.
[0020] Preferably, during the centrifugation process in S4, the rotation speed is 6000-8000 r / min and the time is 5-10 min.
[0021] Preferably, in the washing process of S4, deionized water is first used to wash until neutral, and then anhydrous ethanol is used to wash 2-3 times.
[0022] Preferably, the mass ratio of the mixture of nickel sulfate hexahydrate, deionized water, sodium citrate, sodium hypophosphite, and activated titanium carbide in S4 is (10-12):(400-500):(5-10):(10-12):10.
[0023] A method for preparing the lead-calcium-tin-aluminum multi-element alloy as described above includes the following steps: Step 1: Take a portion of the formula amount of lead and add it to the furnace. Under the protection of argon, heat it to 480-520℃ at a heating rate of 5-10℃ / min. After the lead is completely melted, add indium and stir for 5-10 min at a stirring speed of 30-50 r / min, then add tellurium and stir for 10-20 min, and then add modified titanium carbide and stir for 15-30 min to obtain the reinforced phase composite master alloy. Step 2: Add the remaining amount of lead to the furnace and heat it to 500-550℃ at a heating rate of 5-10℃ / min under an argon protective atmosphere. After the lead is completely melted, add aluminum and stir at a stirring speed of 10-20r / min for 20-30min. Then add tin and stir at a stirring speed of 30-50r / min for 10-20min. After that, heat it to 550-600℃ at a heating rate of 5-10℃ / min and add calcium and stir at a stirring speed of 5-15r / min for 10-20min to obtain the Pb-Ca-Sn-Al matrix alloy melt. Step 3: Add the reinforcing phase composite master alloy to the Pb-Ca-Sn-Al matrix alloy melt, heat to 480-520℃ at a heating rate of 5-10℃ / min, stir at a stirring speed of 40-60r / min for 10-20min, let stand for 5-10min, remove surface slag, cool, and obtain lead-calcium-tin-aluminum multi-element alloy.
[0024] Preferably, the amount of lead in step one is 10%-20% of the total weight of the formulation.
[0025] Preferably, the remaining amount of lead in step two is 80%-90% of the total weight of the formula.
[0026] Application of a lead-calcium-tin-aluminum multi-element alloy in lead-acid battery grids.
[0027] (iii) Beneficial technical effects Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses modified titanium carbide as a reinforcing phase to introduce a lead-calcium-tin-aluminum multi-element alloy system. Titanium carbide has a high melting point, excellent chemical stability, and high hardness, and can serve as a heterogeneous nucleation site to promote grain refinement and inhibit abnormal grain growth. At the same time, titanium carbide can form a dispersed reinforcing phase in the alloy matrix, which restricts grain boundary migration through pinning, improves the stability of the alloy structure, and improves the structural stability of the grid material during long-term charge-discharge cycles. This invention modifies the surface of titanium carbide by electroless nickel plating, and utilizes the good wettability of nickel with lead-based melts to improve the problems of poor wetting, easy agglomeration, and weak interfacial bonding of titanium carbide in liquid lead. Nano-titanium carbide is added to anhydrous ethanol for ultrasonic dispersion to fully separate the agglomerated nano-titanium carbide and increase the surface exposure of the particles. Then, hydrochloric acid solution is added for acid treatment to remove impurities and weakly bound oxides on the surface of nano-titanium carbide and improve the surface activity of the particles. Further, the pretreated titanium carbide is added to stannous chloride solution to make Sn 2+ Adsorbed onto the surface of nano-titanium carbide, a sensitized layer is formed, providing reduction sites for subsequent palladium activation. Subsequently, it is added to a palladium chloride solution, utilizing Sn... 2+ With Pd 2+ The redox reaction between the two causes Pd to deposit on the surface of titanium carbide, forming uniformly distributed catalytic active centers, providing a nucleation basis for the electroless nickel plating reaction. Subsequently, the activated titanium carbide mixture is added to the electroless nickel plating solution, and under the reduction action of sodium hypophosphite, Ni... 2+ Under Pd catalysis, reduction deposition occurs, and some phosphorus elements enter the coating to form a Ni-P coating layer. Nickel, with its good metallic properties and electrical conductivity, improves the wetting performance between titanium carbide and lead-based melts, reduces the agglomeration of the reinforcing phase, and increases the interfacial bonding strength between titanium carbide and the lead matrix, thus facilitating more uniform dispersion of titanium carbide within the alloy. Therefore, by acid treatment, sensitization, activation, and electroless nickel plating, a metallic nickel transition layer is constructed on the surface of titanium carbide, enabling a good interfacial bond between the ceramic reinforcing phase and the metal matrix. This facilitates the grain refinement and reinforcing effects of titanium carbide, improving the microstructure stability of the lead-based alloy.
[0028] (2) In the preparation process of the lead-calcium-tin-aluminum multi-element alloy of the present invention, a composite master alloy containing indium, tellurium, and modified titanium carbide is first constructed, so that trace alloying elements and reinforcing phases are pre-dispersed in part of the lead matrix, avoiding the problems of element segregation and reinforcing phase agglomeration caused by density differences, insufficient interfacial wettability, and excessively high local concentrations during the direct addition of a large amount of lead liquid. Among them, indium, as a trace alloying control element, can delay the passivation trend of the alloy, reduce the corrosion rate, and promote the formation of conductive corrosion film. Tellurium can refine grains, prevent recrystallization of lead alloy, improve the structural stability of alloy, and at the same time reduce the tendency of grain boundary corrosion and improve the corrosion resistance of alloy. Modified titanium carbide, as a reinforcing phase, can promote the grain refinement of lead matrix and improve the mechanical properties of alloy through particle strengthening; at the same time, the nickel coating layer on the surface of titanium carbide can improve the wettability between ceramic particles and lead liquid, improve the interfacial bonding strength between reinforcing phase and matrix, and make titanium carbide more uniformly dispersed in lead-based alloy. Subsequently, a Pb-Ca-Sn-Al matrix alloy melt was prepared, with lead as the base metal providing a continuous matrix structure. Calcium forms a reinforcing structure with lead, improving the alloy's hardness and creep resistance. Tin improves the alloy's machinability and corrosion resistance, while also enhancing melt flowability, which is beneficial for the uniform dispersion of subsequent reinforcing phases. Aluminum reduces calcium oxidation loss, improving the alloy's corrosion resistance and service life. In the preparation of the Pb-Ca-Sn-Al matrix alloy melt, aluminum and tin are added first to uniformly disperse them in the lead melt and improve melt homogeneity. Adding calcium then reduces its residence time in the high-temperature melt, lowering calcium oxidation loss and improving the effective utilization of calcium strengthening. Simultaneously, aluminum further improves melt stability and reduces the formation of coarse reinforcing phases. Finally, the reinforcing phase composite master alloy is added to the Pb-Ca-Sn-Al matrix alloy melt, further ensuring the uniform distribution of the modified titanium carbide reinforcing phase, indium, and tellurium within the multi-component alloy system. During solidification, titanium carbide promotes grain refinement, and the Ca-Sn-Al elements form a multi-element strengthening structure, improving the matrix strength. Simultaneously, tin, indium, and tellurium participate in the formation and stabilization of the corrosion film. Tin enhances film stability, indium improves film density, and tellurium improves grain boundary corrosion resistance. These three elements work synergistically to reduce the corrosion rate and improve cycle stability. Through the synergistic effects of phase strengthening, grain boundary regulation, and corrosion film stabilization, a grid alloy material with high mechanical properties, excellent corrosion resistance, and long service life is ultimately obtained. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Example 1
[0030] A method for preparing modified titanium carbide includes the following steps: S1. Add 1 part of 80nm nano-titanium carbide to 10 parts of anhydrous ethanol, ultrasonically disperse for 20 min, add 10 parts of 0.2mol / L hydrochloric acid solution, stir at 20℃ for 60 min, after the reaction is completed, centrifuge at 6000r / min for 10 min, wash with deionized water until neutral, and dry at 60℃ for 24 h to obtain pretreated titanium carbide. S2. Disperse 0.3 parts of stannous chloride in 25 parts of 1 mol / L hydrochloric acid solution, add 1 part of the pretreated titanium carbide, stir at 20°C for 30 min, centrifuge at 6000 r / min for 10 min, wash twice with deionized water to obtain sensitized titanium carbide mixture. S3. Disperse 0.03 parts of palladium chloride in 25 parts of 0.5 mol / L hydrochloric acid solution, add 1 part of the sensitized titanium carbide mixture, stir at 20℃ for 25 min, centrifuge at 6000 r / min for 10 min, wash twice with deionized water to obtain activated titanium carbide mixture. S4. Disperse 10 parts of nickel sulfate hexahydrate in 400 parts of deionized water, add 5 parts of sodium citrate and 10 parts of sodium hypophosphite in sequence, adjust the pH of the system to 8 with 25% ammonia water to obtain a chemical nickel plating solution, add 10 parts of the above activated titanium carbide mixture to the chemical nickel plating solution, react at 75℃ for 80 min, after the reaction is completed, centrifuge at 6000 r / min for 10 min, wash with deionized water until neutral, then wash twice with anhydrous ethanol, and dry at 60℃ for 24 h to obtain modified titanium carbide. Example 2
[0031] A method for preparing modified titanium carbide includes the following steps: S1. Add 1 part of nano-titanium carbide with a particle size of 100 nm to 13 parts of anhydrous ethanol, ultrasonically disperse for 25 min, add 13 parts of 0.35 mol / L hydrochloric acid solution, stir at 25 °C for 50 min, after the reaction is completed, centrifuge at 7000 r / min for 7 min, wash with deionized water until neutral, and dry at 70 °C for 18 h to obtain pretreated titanium carbide. S2. Disperse 0.5 parts of stannous chloride in 32 parts of 2mol / L hydrochloric acid solution, add 1 part of the pretreated titanium carbide, stir at 25℃ for 22min, centrifuge at 7000r / min for 7min, wash 3 times with deionized water to obtain sensitized titanium carbide mixture. S3. Disperse 0.06 parts of palladium chloride in 32 parts of 0.8 mol / L hydrochloric acid solution, add 1 part of the sensitized titanium carbide mixture, stir at 25°C for 20 min, centrifuge at 7000 r / min for 7 min, wash 3 times with deionized water to obtain activated titanium carbide mixture. S4. Disperse 11 parts of nickel sulfate hexahydrate in 450 parts of deionized water, add 7 parts of sodium citrate and 11 parts of sodium hypophosphite in sequence, adjust the pH of the system to 9 with 26% ammonia water to obtain a chemical nickel plating solution, add 10 parts of the activated titanium carbide mixture to the chemical nickel plating solution, react at 82℃ for 70 min, after the reaction is completed, centrifuge at 7000 r / min for 7 min, wash with deionized water until neutral, then wash with anhydrous ethanol 3 times, and dry at 70℃ for 18 h to obtain modified titanium carbide. Example 3
[0032] A method for preparing modified titanium carbide includes the following steps: S1. Add 1 part of nano-titanium carbide with a particle size of 120 nm to 15 parts of anhydrous ethanol, ultrasonically disperse for 30 min, add 15 parts of 0.5 mol / L hydrochloric acid solution, stir at 30 °C for 40 min, after the reaction is completed, centrifuge at 8000 r / min for 5 min, wash with deionized water until neutral, and dry at 80 °C for 12 h to obtain pretreated titanium carbide. S2. Disperse 0.8 parts of stannous chloride in 40 parts of 3mol / L hydrochloric acid solution, add 1 part of the pretreated titanium carbide, stir at 30℃ for 15 min, centrifuge at 8000 r / min for 5 min, wash 3 times with deionized water to obtain sensitized titanium carbide mixture. S3. Disperse 0.08 parts of palladium chloride in 40 parts of 1 mol / L hydrochloric acid solution, add 1 part of the sensitized titanium carbide mixture, stir at 30℃ for 15 min, centrifuge at 8000 r / min for 5 min, wash 3 times with deionized water to obtain activated titanium carbide mixture. S4. Disperse 12 parts of nickel sulfate hexahydrate in 500 parts of deionized water, add 10 parts of sodium citrate and 12 parts of sodium hypophosphite in sequence, adjust the pH of the system to 10 with 28% ammonia water to obtain a chemical nickel plating solution, add 10 parts of the above activated titanium carbide mixture to the chemical nickel plating solution, react at 90℃ for 60 min, after the reaction is completed, centrifuge at 8000 r / min for 5 min, wash with deionized water until neutral, then wash with anhydrous ethanol 3 times, and dry at 80℃ for 12 h to obtain modified titanium carbide. Example 4
[0033] A method for preparing a lead-calcium-tin-aluminum multi-element alloy includes the following steps: Step 1: Add 10% of the formula amount of lead to the furnace and heat it to 480°C at a heating rate of 5°C / min under an argon protective atmosphere. After the lead is completely melted, add 0.02% indium and stir for 10 min at a stirring speed of 30 r / min, then add 0.01% tellurium and stir for 20 min, and then add 0.1% modified titanium carbide and stir for 30 min to obtain the reinforced phase composite master alloy. Step 2: Add 90% of the formula amount of lead to the furnace. Under the protection of argon, heat the furnace to 500°C at a heating rate of 5°C / min. After the lead is completely melted, add 0.01% aluminum at a stirring speed of 10 r / min and stir for 30 min. Then add 1.2% tin at a stirring speed of 30 r / min and stir for 20 min. After that, heat the furnace to 550°C at a heating rate of 5°C / min and add 0.06% calcium at a stirring speed of 5 r / min and stir for 20 min to obtain the Pb-Ca-Sn-Al matrix alloy melt. Step 3: Add the reinforced phase composite master alloy to the Pb-Ca-Sn-Al matrix alloy melt, heat to 480°C at a heating rate of 5°C / min, stir for 20 min at a stirring speed of 40 r / min, let stand for 5 min, remove surface slag, and cool to obtain lead-calcium-tin-aluminum multi-element alloy. Example 5
[0034] A method for preparing a lead-calcium-tin-aluminum multi-element alloy includes the following steps: Step 1: Add 13% of the formula amount of lead to the furnace and heat it to 490°C at a heating rate of 7°C / min under an argon protective atmosphere. After the lead is completely melted, add 0.04% indium and stir for 8 minutes at a stirring speed of 35 r / min, then add 0.02% tellurium and stir for 17 minutes, and then add 0.15% modified titanium carbide and stir for 25 minutes to obtain the reinforced phase composite master alloy. Step 2: Add 87% of the formula amount of lead to the furnace. Under an argon protective atmosphere, heat the furnace to 515°C at a heating rate of 7°C / min. After the lead is completely melted, add 0.015% aluminum at a stirring speed of 13 r / min and stir for 27 min. Then add 1.5% tin at a stirring speed of 35 r / min and stir for 17 min. After that, heat the furnace to 565°C at a heating rate of 7°C / min and add 0.07% calcium at a stirring speed of 8 r / min and stir for 17 min to obtain the Pb-Ca-Sn-Al matrix alloy melt. Step 3: Add the reinforced phase composite master alloy to the Pb-Ca-Sn-Al matrix alloy melt, heat to 490°C at a heating rate of 7°C / min, stir for 17 min at a stirring speed of 45 r / min, let stand for 7 min, remove surface slag, cool, and obtain lead-calcium-tin-aluminum multi-element alloy. Example 6
[0035] A method for preparing a lead-calcium-tin-aluminum multi-element alloy includes the following steps: Step 1: Add 17% of the formula amount of lead to the furnace and heat it to 510°C at a heating rate of 8°C / min under an argon protective atmosphere. After the lead is completely melted, add 0.06% indium and stir for 7 min at a stirring speed of 45 r / min, then add 0.03% tellurium and stir for 13 min, and then add 0.25% modified titanium carbide and stir for 20 min to obtain the reinforced phase composite master alloy. Step 2: Add 83% of the formula amount of lead to the furnace and heat it to 535°C at a heating rate of 8°C / min under an argon protective atmosphere. After the lead is completely melted, add 0.025% aluminum and stir for 23 min at a stirring speed of 17 r / min. Then add 1.8% tin and stir for 13 min at a stirring speed of 45 r / min. After that, heat it to 585°C at a heating rate of 8°C / min and add 0.09% calcium and stir for 13 min at a stirring speed of 12 r / min to obtain the Pb-Ca-Sn-Al matrix alloy melt. Step 3: Add the reinforced phase composite master alloy to the Pb-Ca-Sn-Al matrix alloy melt, heat to 510°C at a heating rate of 8°C / min, stir for 13 min at a stirring speed of 55 r / min, let stand for 8 min, remove surface slag, cool, and obtain lead-calcium-tin-aluminum multi-element alloy. Example 7
[0036] A method for preparing a lead-calcium-tin-aluminum multi-element alloy includes the following steps: Step 1: Add 20% of the formula amount of lead to the furnace and heat it to 520°C at a heating rate of 10°C / min under an argon protective atmosphere. After the lead is completely melted, add 0.08% indium and stir for 5 min at a stirring speed of 50 r / min, then add 0.04% tellurium and stir for 10 min, and then add 0.3% modified titanium carbide and stir for 15 min to obtain the reinforced phase composite master alloy. Step 2: Add 80% of the formula amount of lead to the furnace. Under an argon protective atmosphere, heat the furnace to 550°C at a heating rate of 10°C / min. After the lead is completely melted, add 0.03% aluminum at a stirring speed of 20 r / min and stir for 20 min. Then add 2% tin at a stirring speed of 50 r / min and stir for 10 min. After that, heat the furnace to 600°C at a heating rate of 10°C / min and add 0.1% calcium at a stirring speed of 15 r / min and stir for 10 min to obtain the Pb-Ca-Sn-Al matrix alloy melt. Step 3: Add the reinforced phase composite master alloy to the Pb-Ca-Sn-Al matrix alloy melt, heat to 520°C at a heating rate of 10°C / min, stir for 10 min at a stirring speed of 60 r / min, let stand for 10 min, remove surface slag, cool, and obtain lead-calcium-tin-aluminum multi-element alloy.
[0037] Comparative Example 1 A method for preparing a lead-calcium-tin-aluminum multi-element alloy, compared with Example 6, differs in that: in step one, indium is replaced with an equal amount of lead, while the other components and preparation method are completely consistent with Example 6.
[0038] Comparative Example 2 A method for preparing a lead-calcium-tin-aluminum multi-element alloy, compared with Example 6, differs in that: in this comparative example, tellurium is replaced with an equal amount of lead in step one, while the other components and preparation methods are completely consistent with Example 6.
[0039] Comparative Example 3 A method for preparing a lead-calcium-tin-aluminum multi-element alloy, compared with Example 6, differs in that: in this comparative example, the modified titanium carbide in step one is replaced with an equal amount of titanium carbide, while the other components and preparation methods are completely consistent with Example 6.
[0040] Comparative Example 4 A method for preparing a lead-calcium-tin-aluminum multi-element alloy, compared with Example 6, differs in that: in this comparative example, the modified titanium carbide in step one is replaced with an equal amount of lead, while the other components and preparation method are completely consistent with Example 6.
[0041] The lead-calcium-tin-aluminum multi-element alloys obtained in Examples 4-7 and Comparative Examples 1-4 were heated to 480°C and melted. They were then cast into a grid mold with a preheating temperature of 180°C under an argon protective atmosphere and allowed to solidify naturally at room temperature to obtain a lead-acid battery grid, which is referred to as Experimental Examples 1-8. The lead-acid battery grids prepared in Examples 1-8 were subjected to relevant performance tests, and the test methods are as follows: (1) Tensile strength test: The sample size was set to 90mm×10mm×1.5mm, the loading speed was 30mm / min, and the tensile strength of the sample was tested using a universal testing machine; (2) Hardness test: Hardness analysis was performed using a microhardness tester. The test force was set to 10N. Six indentation tests were performed in different areas of the sample, and the average value was taken as the final result. (3) Corrosion rate test: The corrosion rate of the sample was tested using the weight loss method. The sample was subjected to a constant current density of 10 mA / cm². 2 After polarization for 72 hours under certain conditions, the surface oxide layer was removed, rinsed with anhydrous ethanol, dried, and weighed. The corrosion rate was then calculated. The test results are shown in Table 1: Table 1 Experimental Example 1 50 20.8 0.92 Experimental Example 2 56 22.8 0.84 Experimental Example 3 62 25.1 0.77 Test Example 4 60 24.6 0.75 Experimental Example 5 53 21.5 1.01 Experimental Example 6 49 19.6 1.03 Experimental Example 7 51 21.2 0.95 Experimental Example 8 43 17.2 1.18 As shown in Table 1, the lead-acid battery grids prepared in Examples 1-4 all exhibit high mechanical properties and low corrosion rates. Among them, the lead-acid battery grid prepared in Example 3 demonstrates the best overall performance, with a tensile strength of 62 MPa, a Vickers hardness of 25.1 HV, and a corrosion rate reduced to 0.77 g / (m²). 2 (h) Compared to Example 3, Example 5 does not contain indium, thus lacking indium's regulatory effect on the alloy's grain boundary structure and corrosion film stability. This reduces the microstructural stability of the grid alloy and decreases the density of the corrosion film during corrosion, leading to a decrease in the material's tensile strength, hardness, and corrosion resistance. Example 6 does not contain tellurium, thus lacking tellurium's effect on alloy grain refinement and grain boundary stabilization. This weakens the grain refinement effect during alloy solidification, reduces the stability of the grain boundary region, and leads to a decrease in the mechanical properties of the grid material. Simultaneously, the corrosive medium is more likely to erode along the grain boundaries, increasing the corrosion rate. In Example 7, modified titanium carbide was replaced with an equal amount of titanium carbide. Because the titanium carbide particles lack a nickel-phosphorus coating layer, the wettability between the reinforcing phase and the lead-based melt is poor, easily leading to particle agglomeration and insufficient interfacial bonding. This makes it difficult for the titanium carbide reinforcing phase to be uniformly dispersed in the alloy matrix, reducing the particle strengthening and grain refinement effect, resulting in a decrease in the tensile strength, hardness, and corrosion resistance of the grid material. In Experiment 8, no modified titanium carbide was added, resulting in the absence of heterogeneous nucleation and particle pinning strengthening effects. During alloy solidification, the grain size increased, the microstructure uniformity decreased, and an effective reinforcing structure could not be formed, leading to a decline in the mechanical properties of the grid material. Furthermore, due to the lack of titanium carbide's ability to improve grain boundaries and microstructure stability, the grain boundary regions were more susceptible to corrosion during the corrosion process, further increasing the corrosion rate.
[0042] A lead-acid battery consists of a positive grid, a negative grid, a separator, an electrolyte, and a casing. The lead-acid battery grids obtained in Examples 1-8 are used as the positive grids, with a positive lead paste coated on their surface. The positive lead paste is a mixture of lead powder, red lead, graphite powder, short glass fibers, sulfuric acid, and deionized water. A conventional lead-calcium alloy grid is used as the negative grid, with a negative lead paste coated on its surface. The negative lead paste is a mixture of lead powder, barium sulfate, lignin, humic acid, short glass fibers, sulfuric acid, and deionized water. The separator is a microporous polyethylene separator. The electrolyte has a density of 1.28 g / cm³. 3 A sulfuric acid solution; the casing is made of ABS engineering plastic, and after assembly, a lead-acid battery is obtained, denoted as sample 1-8; The lead-acid batteries prepared in samples 1-8 were subjected to relevant performance tests, and the test methods are as follows: (4) Cycle life test: According to GB / T 22199.1-2025 "Valve-regulated lead-acid batteries for electric bicycles - Part 1: Technical conditions", after fully charging the lead-acid battery, discharge it at a current of 1.0I2 for 1.6 hours in an environment of 25±2℃, and then charge it at a voltage of 2.467V / cell (current limit of 0.35I2). When the charging current is less than 0.05I2 or the charging time reaches 6 hours, let it stand for 5 minutes, and then charge it at 2.317V / cell for 3 hours. This is one cycle. The test is terminated when the discharge voltage is lower than 1.750V / cell for 3 consecutive times. The test results are shown in Table 2: Table 2 Cycle life (times) 352 386 415 407 326 318 345 275 As shown in Table 2, the lead-acid batteries prepared in samples 1-4 all exhibited good cycle stability. Sample 3 achieved a cycle life of 415 cycles. Compared to sample 3, sample 5, due to the absence of indium in the positive grid, suffered from reduced alloy corrosion film control, making the positive grid more susceptible to corrosion during repeated charge-discharge cycles. This decreased grid structural integrity and reduced active material carrying capacity, leading to a shorter battery cycle life. Sample 6, lacking tellurium, experienced weakened alloy grain refinement and reduced grain boundary stability. During long-term electrochemical cycling, corrosive media diffused more easily along grain boundaries, accelerating grid corrosion failure and reducing battery cycle life. Sample 7 used unmodified titanium carbide instead of modified titanium carbide. Due to poor wettability between titanium carbide and the lead matrix, the uniformity of the reinforcing phase dispersion decreased, and the interfacial bonding strength was insufficient. This resulted in the titanium carbide failing to continuously exert its reinforcing effect during charge-discharge cycles, reducing the grid's resistance to corrosion deformation and ultimately decreasing cycle life. Sample 8 did not contain modified titanium carbide, which lacked the strengthening effect of the alloy structure. The overall mechanical properties and structural stability of the grid were reduced, and corrosion loss and structural degradation were prone to occur during long-term charge and discharge, which accelerated the failure rate of the positive electrode grid and ultimately led to a significant decrease in cycle life.
[0043] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A lead-calcium-tin-aluminum multi-element alloy, characterized in that: It is composed of the following components by mass percentage: calcium 0.06%-0.1%, tin 1.2%-2%, aluminum 0.01%-0.03%, indium 0.02%-0.08%, tellurium 0.01%-0.04%, modified titanium carbide 0.1%-0.3%, with the balance being lead; The modified titanium carbide is a nickel-phosphorus coated titanium carbide composite reinforcing material, which is obtained by depositing a nickel-phosphorus coating layer on the surface of pretreated titanium carbide using a chemical nickel plating process.
2. The lead-calcium-tin-aluminum multi-element alloy according to claim 1, characterized in that: The modified titanium carbide is prepared by the following steps: S1. Add nano-titanium carbide to anhydrous ethanol, ultrasonically disperse for 20-30 min, add hydrochloric acid solution, stir at 20-30℃ for 40-60 min, after the reaction is completed, centrifuge, wash with deionized water until neutral, and dry at 60-80℃ for 12-24 h to obtain pretreated titanium carbide. S2. Disperse stannous chloride in hydrochloric acid solution, add the pretreated titanium carbide, stir at 20-30℃ for 15-30 min, centrifuge, and wash with deionized water 2-3 times to obtain sensitized titanium carbide mixture; S3. Disperse palladium chloride in hydrochloric acid solution, add the sensitized titanium carbide mixture, stir at 20-30℃ for 15-25 min, centrifuge, and wash with deionized water 2-3 times to obtain activated titanium carbide mixture; S4. Disperse nickel sulfate hexahydrate in deionized water, add sodium citrate and sodium hypophosphite in sequence, adjust the pH of the system to 8-10 with ammonia water to obtain a chemical nickel plating solution, add the activated titanium carbide mixture to the chemical nickel plating solution, react at 75-90℃ for 60-80 min, after the reaction is completed, centrifuge, wash, and dry at 60-80℃ for 12-24 h to obtain modified titanium carbide.
3. The lead-calcium-tin-aluminum multi-element alloy according to claim 2, characterized in that: The nano-titanium carbide in S1 has a particle size of 80-120 nm, and the mass ratio of nano-titanium carbide, anhydrous ethanol, and hydrochloric acid solution is 1:(10-15):(10-15).
4. A lead-calcium-tin-aluminum multi-element alloy according to claim 2, characterized in that: The mass ratio of stannous chloride, hydrochloric acid solution, and pretreated titanium carbide in S2 is (0.3-0.8):(25-40):
1.
5. A lead-calcium-tin-aluminum multi-element alloy according to claim 2, characterized in that: The mass ratio of palladium chloride, hydrochloric acid solution, and sensitized titanium carbide mixture in S3 is (0.03-0.08):(25-40):
1.
6. A lead-calcium-tin-aluminum multi-element alloy according to claim 2, characterized in that: The mass ratio of the mixture of nickel sulfate hexahydrate, deionized water, sodium citrate, sodium hypophosphite, and activated titanium carbide in S4 is (10-12):(400-500):(5-10):(10-12):
10.
7. A method for preparing a lead-calcium-tin-aluminum multi-element alloy as described in any one of claims 1-6, characterized in that: Includes the following steps: Step 1: Take a portion of the formula amount of lead and add it to the furnace. Under the protection of argon, heat it to 480-520℃ at a heating rate of 5-10℃ / min. After the lead is completely melted, add indium and stir for 5-10 min at a stirring speed of 30-50 r / min, then add tellurium and stir for 10-20 min, and then add modified titanium carbide and stir for 15-30 min to obtain the reinforced phase composite master alloy. Step 2: Add the remaining amount of lead to the furnace and heat it to 500-550℃ at a heating rate of 5-10℃ / min under an argon protective atmosphere. After the lead is completely melted, add aluminum and stir at a stirring speed of 10-20r / min for 20-30min. Then add tin and stir at a stirring speed of 30-50r / min for 10-20min. After that, heat it to 550-600℃ at a heating rate of 5-10℃ / min and add calcium and stir at a stirring speed of 5-15r / min for 10-20min to obtain the Pb-Ca-Sn-Al matrix alloy melt. Step 3: Add the reinforcing phase composite master alloy to the Pb-Ca-Sn-Al matrix alloy melt, heat to 480-520℃ at a heating rate of 5-10℃ / min, stir at a stirring speed of 40-60r / min for 10-20min, let stand for 5-10min, remove surface slag, cool, and obtain lead-calcium-tin-aluminum multi-element alloy.
8. The method for preparing a lead-calcium-tin-aluminum multi-element alloy according to claim 7, characterized in that: In step one, the amount of lead in the formula is 10%-20% of the formula weight.
9. The method for preparing a lead-calcium-tin-aluminum multi-element alloy according to claim 7, characterized in that: In step two, the remaining amount of lead in the formula is 80%-90% of the formula weight.
10. The application of the lead-calcium-tin-aluminum multi-element alloy according to any one of claims 1-6 in the grid of a lead-acid battery.
Citation Information
Patent Citations
Multi-element alloy for making lead acid accumulator plate grid
CN101237045A
Lead-calcium-tin-aluminum positive grid alloy and preparation method thereof
CN103985879A